KINERJA PUSTAKAWAN PERPUSTAKAAN FISIP UNTAN DALAM PELAYANAN KEPADA PEMUSTAKA - Sapril, Mohammad; Madeten, Sisilya Saman (Universitas Tanjungpura, 2023)
This study aims to determine the Performance of Library Librarians of FISIP Untan in Services to Users. The research method used is a qualitative research method with a descriptive approach. The source of this research data is the library manager of FISIP Untan. Data collection techniques: making observations in the service room, seeing the performance of librarians and paying attention to performance in the service room, conducting interviews with library managers about performance in the service room. The performance of librarians in serving users in the FISIP Untan library environment in the category is very good. Factors that affect the performance of librarians in the FISIP Untan library consist of internal factors, namely inappropriate human resources and external factors, namely the lack of book storage shelves. Obstacles faced by librarians in providing services to users in the FISIP Untan library environment, including indifferent attitude, lack of user compliance with the rules of order and the existence of damaged book collections.